Norway`s competitive advantage over the U.S. starts with the kids - Geier, D. (The Post and Courier, 2019)
The article gives an answer to the question: Why is Norway, a country with a population of only 5.3 million, better at Winter Olympic sports than the United States? may be the difference lis in the youth sports systems of both countries. The secret doesn`t seem to be the methods Norway uses to train its top athletes in the years before they compete on the world stage, but the ways they encourage sports participation for all young children.